(untitled) - Hannam, Joyce (Oxford, 1997)
This is the true story about the death of Karen Silkwood. Her death is a mystery. Was it an accident? We don't know. But somebody does. Somebody out there, in the real world, know her death was an accident, or if it was not. Somebody knows - somebody who is alive and well and living an ordinary life, somewhere in America, and who remembers what really happened...
Keywords: English fiction,English literature; 20th century